The role of Islamic work ethics in influencing organizational commitments mediated by intrinsic motivation of Islamic senior high school teachers - Dhian Pratiwi (Asian Journal of Islamic Management (AJIM), 2019)
Purpose: This study aims to examine the effect of Islamic work ethics in influencing organizational commitment through intrinsic motivation as a mediating variableDesign: Respondents of this study were 85 teachers at some Islamic high schools in Yogyakarta, Indonesia. This study implemented path analysis using SPSS.Findings: The results of this study found that Islamic work ethics has a significant positive effect on organizational commitment. Besides that, intrinsic motivation is proven to be a mediating variable.Originality/value: Work ethics is commonly found as a factor that influence organizational commitment. However, studies related to this topic are still limited in the Islamic context.